Baicalin relieves hypoxia-aroused H9c2 cell apoptosis by activating Nrf2/HO-1-mediated HIF1α/BNIP3 pathway - Hailiang Yu; Bin Chen; Qi Ren (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Background Myocardial ischemia is the main reason for ischemic heart disease. Baicalin is a plant-derived flavonoid with cardio-protective activity. Herein, we tested the influences of baicalin on cardiomyocytes H9c2 apoptosis aroused by hypoxia stimulation.Methods Firstly, H9c2 cells were subjected to hypoxia and/or baicalin exposure. Cell viability and apoptosis, along with hypoxia-inducible factor 1α (HIF1α) and Bcl-2/adenovirus E1B 19-KDa interacting protein 3 (BNIP3) expressions were tested respectively. Then, si-HIF1α was transfected into H9c2 cells to probe whether up-regulation of HIF1α attended to the influences of baicalin on hypoxia-stimulated H9c2 cells. Finally, the regulatory effect of nuclear factor E2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway on HIF1α expression was analyzed.Results Hypoxia exposure aroused H9c2 cell viability reduction and apoptosis. Baicalin mitigated H9c2 cell viability reduction and apoptosis aroused by hypoxia. Moreover, HIF1α/BNIP3 pathway was further activated by baicalin in hypoxia-exposed H9c2 cells. Silencing HIF1α lowered the functions of baicalin on hypoxia-exposed H9c2 cells. Besides, baicalin enhanced hypoxia-caused activation of Nrf2/HO-1 pathway. Activation of Nrf2/HO-1 pathway was associated with the up-regulation of HIF1α and protective functions of baicalin on hypoxia-exposed H9c2 cells.Conclusion Baicalin relieved cardiomyocytes H9c2 apoptosis aroused by hypoxia might be achieved through activating Nrf2/HO-1-mediated HIF1α/BNIP3 pathway.HighlightsBaicalin mitigates H9c2 cell viability loss and apoptosis aroused by hypoxia;Baicalin activates HIF1a/BNIP3 pathway in hypoxia-exposed H9c2 cells;Silencing HIF1α weakens the influences of baicalin on hypoxia-exposed H9c2 cells;Baicalin promotes Nrf2/HO-1 pathway in hypoxia-exposed H9c2 cells;Promotion of Nrf2/HO-1 pathway is related to the up-regulation of HIF1α.